Improving Science Literacy through Virtual Experiments in Inquiry-based Learning: A Quasi-Experimental Analysis on the Concept of Optical Instruments - Citra Aulia Aswari; Iwan Permana Suwarna; Sifa Naulifar (EDUSAINS, 2024)
In PISA 2022, it was shown that Indonesian students' scores declined from 396 in 2018 to 383. This was evident in the 2022 National Assessment, where the science literacy ability at the high school level dropped by 4.59%. The low ability is mainly in optics, particularly optical instruments, indicating that students can only recognize the concept if they understand it. This study aims to determine the effect of inquiry-based learning on science literacy skills and Improvement in science literacy aspects. The research method used quasi-experimental with a nonequivalent control group design. The research population consisted of 199 students of grade XI at SMA Negeri 4 South Tangerang City, with a sample of 70 students: 35 students in class XI IPA 3 (experimental group) and 35 students in class XI IPA 4 (control group). The Mann-Whitney test results (Asymp Sig. 2-tailed < 0.05) showed a significant difference in science literacy skills between the experimental and control groups. The N-gain score indicated increased science literacy skills in the experimental group by 0.3 (medium category), while the control group was 0.10 (low category). Improvement occurred in the competence aspect by 0.33 and the knowledge aspect by 0.33 for the experimental group, while the control group in the competence aspect was 0.10 and the knowledge aspect was 0.13. Inquiry-based learning in this study has an effect and can improve students' science literacy skills.